2008
DOI: 10.1063/1.3000641
|View full text |Cite
|
Sign up to set email alerts
|

Nanophase segregation and water dynamics in hydrated Nafion: Molecular modeling and experimental validation

Abstract: Reported results of coarse-grained molecular dynamics simulations rationalize the effect of water on the phase-segregated morphology of Nafion ionomers. We analyzed density maps and radial distribution functions and correlated them with domain structures, distributions of protogenic side chains, and water transport properties. The mesoscopic structures exhibit spongelike morphologies. Hydrophilic domains of water, protons, and anionic side chains form a random three-dimensional network, which is embedded in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
138
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(147 citation statements)
references
References 78 publications
9
138
0
Order By: Relevance
“…Atomistic molecular dynamics (MD) simulations [27][28][29][30][31][32]34,37 have served as the focal point of membrane simulation studies. Other approaches such dissipative particle dynamics (DPD) simulations 50,53,55 and mean-field approaches 56 have helped expanding the time and length scale of atomistic simulations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Atomistic molecular dynamics (MD) simulations [27][28][29][30][31][32]34,37 have served as the focal point of membrane simulation studies. Other approaches such dissipative particle dynamics (DPD) simulations 50,53,55 and mean-field approaches 56 have helped expanding the time and length scale of atomistic simulations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These phenomena are critical for high membrane proton conductivity and high PEMFC power density. 15,16 A wealth of analytical techniques has been used to obtain morphological and structural information about Nafion  , including X-ray and neutron scattering, 13,14,[17][18][19][20][21][22] electron microscopy, 23 atomic force microscopy (AFM), [24][25][26][27][28][29] numerical modeling, 30,31 etc. Numerous studies of the ionic conductivity of Nafion ® have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Equations (15)(16)(17)(18) with T in Kelvin were used for diffusion in the Nafion phase [26] and water phase [27]. Water diffusion D'…”
Section: Gas Permeabilitymentioning
confidence: 99%
“…These jumping rules ensured that the diffusion of the gas particles within both phases was well described, and that during the simulations, the gas particle concentration within each phase matched exactly the experimental pure phase component solubility. The gas diffusion constants within the membrane were obtained by multiplication of the slopes derived from the MSD curves with the diffusion constant of oxygen and hydrogen in the pure water phase given by Equations (17) and (18), respectively. The permeability K was calculated by multiplying of the thus-obtained diffusion constant with the solubility values given by Equation (12).…”
Section: Gas Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation